Investigating the factors influencing the shear behaviour of 0/90∘ non-crimp fabrics to form a reference shear test. (August 2021) - Krishnappa, Likith; Ohlendorf, Jan-Hendrik; Brink, Michael; Thoben, Klaus-Dieter
Technical textiles have the ability to deform under load by shearing, which distinguishes them from thin sheet materials such as paper. This particular property helps them to deform and take the shape of the complex part that they were intended to create. Draping, flexibility and handling of technical textiles are greatly affected by their shearing behaviour. In this paper, the influence that factors such as stitch (i.e., presence or absence of it), testing speed and the pre-tension force applied have on the shear behaviour of 0/90∘ technical textile is studied to form a reference test. To achieve this, 0/90∘ technical textile samples in two different forms are prepared and subjected to the Trellis picture frame test. It was observed that the presence of stitch greatly affected the critical shear angle and the maximum shear force experienced by the textile. Increase in testing speeds and pre-tension force also increased the shear force experienced by it. However, the critical shear angle decreased with the increase in testing speed, while the value of pre-tension force applied had no effect on the critical shear angle.